KETERAMPILAN GURU DALAM MEMBERIKAN PENGUATAN PADA PROSES PEMBELAJARAN FIKIH KELAS VII DI MTS TI TARUSAN KAMANG - Yanti, Rahma; Charles, Charles; Aprison, Wedra; Fauzan, Fauzan (JURNAL PENDIDIKAN DAN KEGURUAN, 2024)
The success or failure of a teacher in conveying learning depends on the way the teacher manages the learning. Classroom management is the teacher's skill in creating and maintaining optimal learning conditions. This research is motivated by the teacher's ability to provide reinforcement in the learning process. The purpose of this study was to describe the application of teacher skills in providing reinforcement to the learning process of Jurisprudence Class VII at MTs TI Tarusan Kamang. This research is a qualitative research with a descriptive research type. The research location is MTs TI Tarusan Kamang. The subject used in this study was the VII th grade Jurisprudence teacher. The informants in this study were class VII teachers and class VII student representatives. The object of this research is the skill of giving reinforcement. Data collection techniques used are observation, interviews, and documentation. Data is analyzed through data reduction, data display, and data verification. Data validity checking technique uses data triangulation. The results of the study show that the teacher applies reinforcement skills in learning with various components which include verbal reinforcement and non-verbal reinforcement. Verbal reinforcement is applied with two components, namely reinforcement with words and reinforcement with sentences. The application of non-verbal reinforcement has six components, namely reinforcement by using cues, reinforcement by approaching, reinforcement by touch, reinforcement with fun activities, reinforcement in the form of symbols or objects, incomplete and full reinforcement. In giving reinforcement the teacher also pays attention to the principles of giving reinforcement.